1996
DOI: 10.1063/1.362420
|View full text |Cite
|
Sign up to set email alerts
|

Electro-refraction and electro-absorption in poled polymer Fabry–Perot étalons

Abstract: Poling and orientational relaxation: Comparison of nonlinear optical mainchain and sidechain polymers Photorefractive composite materials with bifunctional charge transporting secondorder nonlinear optical chromophores Large nonbiased alloptical bistability in an electroabsorption modulator using pinip diode and asymmetric Fabry-Perot cavity structureWe present a simple experimental procedure that uses a slowly rotating étalon to measure simultaneously the electro-refraction and electro-absorption in a poled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Eldering et al [12] demonstrated the use of a transmission mode FP etalon with angle scanning at a fixed wavelength to study second-order nonlinear properties of polymer materials by fitting numerical data based on a relatively simple analysis of the multilayer structure requiring two semitransparent electrodes. O'Brien et al [13] introduced a variation of the transmission FP technique using a thick glass substrate. The use of FP analysis was later applied by Pretre et al [14] to decal-deposited reflection FP structures in order to measure complex linear optical and electro-optic parameters as well as to characterize the inverse piezoelectric contribution.…”
Section: Open Accessmentioning
confidence: 99%
See 4 more Smart Citations
“…Eldering et al [12] demonstrated the use of a transmission mode FP etalon with angle scanning at a fixed wavelength to study second-order nonlinear properties of polymer materials by fitting numerical data based on a relatively simple analysis of the multilayer structure requiring two semitransparent electrodes. O'Brien et al [13] introduced a variation of the transmission FP technique using a thick glass substrate. The use of FP analysis was later applied by Pretre et al [14] to decal-deposited reflection FP structures in order to measure complex linear optical and electro-optic parameters as well as to characterize the inverse piezoelectric contribution.…”
Section: Open Accessmentioning
confidence: 99%
“…Equations (9), (11), and (12) are all that is needed to determine r 13 and r 33 in this simplified model. In the next section, we explore the validity of using Equation (6) for the practical multilayer structure of Figure 2(b).…”
Section: Simplified Analysis Based On Ideal Three Layer Fabry-perot Smentioning
confidence: 99%
See 3 more Smart Citations